Copolyamide hot melt adhesive as well as preparation method and application thereof

By introducing cyclic diamines and ether diamines into the copolyamide hot melt adhesive and reacting with long carbon chain diamines and acids with specific proportions, the existing hot melt adhesive bonding strength and water washing resistance are solved, and a copolyamide hot melt adhesive with excellent bonding and water washing resistance is prepared.

CN119505794APending Publication Date: 2025-02-25NANTONG XIEXIN HOT MELT ADHESIVE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411846929.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing copolyamide hot melt adhesives are insufficient in bonding to specially treated fabrics and wash resistance, which cannot meet the high requirements of textile preparation.

Method used

A copolyamide hot melt adhesive was prepared by introducing cyclic diamines and ether diamines, and salt-forming reaction and polymerization with long carbon chain diamines and dibasic acids through specific ratios.

Benefits of technology

It achieves excellent adhesive properties and high washing resistance to special fabrics, improves peel strength and reduces washing loss rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005189470990000061
    Figure BDA0005189470990000061
  • Figure BDA0005189470990000071
    Figure BDA0005189470990000071
  • Figure BDA0005189470990000081
    Figure BDA0005189470990000081
Patent Text Reader

Abstract

The invention belongs to the technical field of organic synthesis, and discloses a copolyamide hot melt adhesive as well as a preparation method and application thereof. The preparation method of the copolyamide hot melt adhesive comprises the following steps: mixing lactam, binary acid, diamine, an antioxidant and water, and carrying out salt forming reaction to obtain a first product; the first product is subjected to a polymerization reaction, standing is performed after the polymerization reaction is finished, and the copolyamide hot melt adhesive is obtained. The copolyamide hot melt adhesive is characterized in that the copolyamide hot melt adhesive which has a melting point of 95-115 DEG C and is suitable for difficult-to-adhere fabrics is synthesized through a specific raw material formula design, and the copolyamide hot melt adhesive is used for adhering specially treated textile products and has excellent washing resistance and peel strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organic synthesis, and in particular to a copolyamide hot melt adhesive and a preparation method and application thereof. Background Art

[0002] With the development of society and its needs, people's requirements for food, clothing, housing and transportation have increased, especially the comfort of clothing and the requirements for adapting to various environments. The textile industry has developed various special fabrics, acetate fabrics (with silk-like luster and feel and moderate price, deeply loved by consumers) and triple-proof fabrics (waterproof, windproof, dustproof; the surface of the fabric is easier to clean and keep clean. At the same time, the windproof performance of the triple-proof fabric can effectively prevent the invasion of tiny particles such as dust and sewage, and protect the skin from pollution. Due to its unique properties, it is often used in outdoor sports, firefighting, aerospace, medical and other industries).

[0003] Since special fabrics are specially treated during the textile preparation process, conventional copolyamides are synthesized using aliphatic long-chain amines and acids, and the resulting hot-melt adhesive strength and adhesive peel strength after washing cannot meet the requirements. Summary of the invention

[0004] The purpose of the present invention is to provide a copolyamide hot melt adhesive and a preparation method and application thereof, by introducing cyclic diamines and ether diamines, and synthesizing copolyamide hot melt adhesives with long carbon chain diamines and dibasic acids in a certain ratio to solve the problem that the existing specially treated fabrics have poor bonding strength and are not resistant to water washing.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a copolyamide hot melt adhesive, comprising the following steps:

[0007] The lactam, the dibasic acid, the diamine, the antioxidant and water are mixed to form a salt to obtain a first product;

[0008] The first product is subjected to a polymerization reaction, and after the polymerization reaction is completed, the product is allowed to stand to obtain a copolyamide hot melt adhesive.

[0009] Preferably, the lactam is caprolactam;

[0010] The dibasic acid is a mixture of adipic acid, succinic acid, sebacic acid, dodecane diacid and tetradecane diacid;

[0011] The diamine is a mixture of hexamethylenediamine, pentamethylenediamine, polyetheramine, 4,4-diaminodicyclohexylmethane, decanediamine and dodecyldiamine.

[0012] Preferably, the antioxidant is at least one of 1098, 168, and 1010;

[0013] The conditions of the salt-forming reaction are as follows: pressure of 0.5-0.6 MPa, temperature of 170-180° C., and time of 2-3 h.

[0014] Preferably, the molar ratio of the diamine to the lactam is 1:0.5-0.8;

[0015] The molar ratio of the diamine to the dibasic acid is 1.02:1;

[0016] The mass of the antioxidant is 0.2-0.5% of the total mass of the lactam, the dibasic acid and the diamine;

[0017] The mass of the water is 5-8% of the total mass of the lactam, the dibasic acid and the diamine.

[0018] Preferably, the molar ratio of adipic acid to succinic acid in the dibasic acid is 1:0.1-0.2;

[0019] The molar ratio of adipic acid to sebacic acid in the dibasic acid is 1:1.1-1.5;

[0020] The molar ratio of adipic acid to dodecane diacid in the dibasic acid is 1:1.5-1.8;

[0021] The molar ratio of adipic acid to tetradecane diacid in the dibasic acid is 1:1.2-1.5.

[0022] In the present invention, the product has excellent bonding strength and water washability when the amount of adipic acid, succinic acid, sebacic acid, dodecane diacid and tetradecane diacid in the dibasic acid is within the range defined by the present invention, and too little or too much content affects the performance of the product.

[0023] Preferably, the molar ratio of hexamethylenediamine to pentamethylenediamine in the diamine is 1:0.4-0.6;

[0024] The molar ratio of hexamethylenediamine to polyetheramine (D400) in the diamine is 1:0.2-0.35;

[0025] The molar ratio of hexamethylenediamine to 4,4-diaminodicyclohexylmethane in the diamine is 1:0.1-0.15;

[0026] The molar ratio of hexamethylenediamine to decanediamine in the diamine is 1:0.5-0.6;

[0027] The molar ratio of hexamethylenediamine to dodecyldiamine in the diamine is 1:1.12-1.32.

[0028] In the present invention, the amount of diamines such as hexamethylenediamine, pentamethylenediamine, polyetheramine, 4,4-diaminodicyclohexylmethane, decanediamine and dodecyldiamine is within the range defined by the present invention, and the product has excellent bonding strength and water resistance. Too little or too much content will affect the performance of the product.

[0029] Preferably, the polymerization reaction conditions are: pressure of 1.6-1.7 MPa, temperature of 255-260° C., and time of 3-4 h.

[0030] Preferably, after the polymerization reaction is completed, the process further comprises releasing the pressure to 0 MPa, and the speed of releasing the pressure is 0.005 MPa / 10s;

[0031] The standing time is 1.5 to 2 hours.

[0032] The invention also provides a copolyamide hot melt adhesive prepared by the preparation method of the copolyamide hot melt adhesive.

[0033] The invention also provides an application of the copolyamide hot melt adhesive in fabrics.

[0034] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0035] The innovation of the present invention lies in that a copolyamide hot melt adhesive with a melting point of 95-115°C and suitable for difficult-to-bond fabrics is synthesized through a specific raw material formula design. This adhesive is used for bonding specially treated textile products and has excellent water resistance and peeling strength. DETAILED DESCRIPTION

[0036] The present invention provides a method for preparing a copolyamide hot melt adhesive, comprising the following steps:

[0037] The lactam, the dibasic acid, the diamine, the antioxidant and water are mixed to form a salt to obtain a first product;

[0038] The first product is subjected to a polymerization reaction, and after the polymerization reaction is completed, the product is allowed to stand to obtain a copolyamide hot melt adhesive.

[0039] In the present invention, the lactam is preferably caprolactam.

[0040] In the present invention, the dibasic acid is preferably a mixture of adipic acid, succinic acid, sebacic acid, dodecane diacid and tetradecane diacid.

[0041] In the present invention, the molar ratio of adipic acid to succinic acid in the dibasic acid is preferably 1:0.1 to 0.2, more preferably 1:0.12 to 0.18, and even more preferably 1:0.14 to 0.16.

[0042] In the present invention, the molar ratio of adipic acid to sebacic acid in the dibasic acid is preferably 1:1.1 to 1.5, more preferably 1:1.2 to 1.4, and even more preferably 1:1.25 to 1.3.

[0043] In the present invention, the molar ratio of adipic acid to dodecane diacid in the dibasic acid is preferably 1:1.5-1.8, more preferably 1:1.55-1.75, and even more preferably 1:1.6-1.7.

[0044] In the present invention, the molar ratio of adipic acid to tetradecane diacid in the dibasic acid is preferably 1:1.2-1.5, more preferably 1:1.25-1.45, and even more preferably 1:1.3-1.4.

[0045] In the present invention, the diamine is a mixture of hexamethylenediamine, pentamethylenediamine, polyetheramine, 4,4-diaminodicyclohexylmethane, decanediamine and dodecyldiamine.

[0046] In the present invention, the molar ratio of hexamethylenediamine to pentamethylenediamine in the diamine is preferably 1:0.4-0.6, more preferably 1:0.45-0.55, and more preferably 1:0.5-0.52.

[0047] In the present invention, the molar ratio of hexamethylenediamine to polyetheramine in the diamine is preferably 1:0.2-0.35, more preferably 1:0.22-0.32, and more preferably 1:0.25-0.3;

[0048] The polyetheramine is preferably polyetheramine D400.

[0049] In the present invention, the molar ratio of hexamethylenediamine to 4,4-diaminodicyclohexylmethane in the diamine is preferably 1:0.1-0.15, more preferably 1:0.11-0.14, and even more preferably 1:0.12-0.13.

[0050] In the present invention, the molar ratio of hexamethylenediamine to decanediamine in the diamine is preferably 1:0.5-0.6, more preferably 1:0.52-0.58, and even more preferably 1:0.55-0.56.

[0051] In the present invention, the molar ratio of hexamethylenediamine to dodecyldiamine in the diamine is preferably 1:1.12-1.32, more preferably 1:1.15-1.3, and more preferably 1:1.2-1.25.

[0052] In the present invention, the molar ratio of the diamine to the lactam is preferably 1:0.5-0.8, more preferably 1:0.52-0.75, and even more preferably 1:0.55-0.6.

[0053] In the present invention, the molar ratio of the diamine to the dibasic acid is preferably 1.02:1.

[0054] In the present invention, the antioxidant is preferably at least one of 1098, 168, and 1010, more preferably one or more of 1098, 168, and 1010, and more preferably one or two of 1098 and 168.

[0055] In the present invention, the conditions for the salt-forming reaction are: the pressure is preferably 0.5-0.6 MPa, more preferably 0.52-0.58 MPa, more preferably 0.55-0.56 MPa; the temperature is preferably 170-180°C, more preferably 172-178°C, more preferably 175-177°C; the time is preferably 2-3 h, more preferably 2.25-2.75 h, more preferably 2.5 h.

[0056] In the present invention, the weight of the antioxidant is preferably 0.2 to 0.5% of the total weight of the lactam, the dibasic acid and the diamine, more preferably 0.25 to 0.45%, and even more preferably 0.3 to 0.4%.

[0057] In the present invention, the mass of the water is preferably 5 to 8% of the total mass of the lactam, the dibasic acid and the diamine, more preferably 5.5 to 7.5%, and even more preferably 6 to 7%.

[0058] In the present invention, the conditions of the polymerization reaction are: the pressure is preferably 1.6-1.7 MPa, more preferably 1.62-1.68 MPa, more preferably 1.65-1.66 MPa; the temperature is preferably 255-260°C, more preferably 256-259°C, more preferably 257-258°C; the time is preferably 3-4 h, more preferably 3.25-3.75 h, more preferably 3.5 h.

[0059] In the present invention, after the polymerization reaction is completed, the pressure is released to 0 MPa, and the speed of the pressure release is preferably 0.005 MPa / 10s.

[0060] In the present invention, the standing time is preferably 1.5 to 2 hours, more preferably 1.75 to 2 hours, and more preferably 2 hours.

[0061] The invention also provides a copolyamide hot melt adhesive prepared by the preparation method of the copolyamide hot melt adhesive.

[0062] The invention also provides an application of the copolyamide hot melt adhesive in fabrics.

[0063] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0064] Example 1

[0065] 3732.390 g (33.030 mol) of caprolactam, 1460.000 g (10.000 mol) of adipic acid, 118.000 g (1.000 mol) of succinic acid, 2424.000 g (12.000 mol) of sebacic acid, 4140.000 g (18.000 mol) of dodecane diacid, 3172.000 g (13.000 mol) of tetradecane diacid, 1740.000 g (15.000 mol) of hexamethylenediamine, 612.000 g (6.000 mol) of pentamethylenediamine, 1500.000 g (3.750 mol) of polyetheramine (D400), 472.5 00g (2.250mol), 1419.000g (8.250mol) of decanediamine, 3960.000g (19.800g) of dodecyl diamine, 61.875g of antioxidant and 1484.993g of water were added into a 50L reactor, the temperature was raised to 100°C and then stirred, the temperature was continued to be raised to 170°C, and the pressure was controlled to 0.5MPa for salt-forming reaction for 3.0h. After the salt-forming reaction was completed, the temperature and pressure were continued to be raised to 260°C and 1.6MPa for polymerization reaction for 3h. After the polymerization reaction was completed, the pressure was released to 0MPa at a rate of 0.005MPa / 10s, and then it was allowed to stand for 1.5h; nitrogen was introduced and the material was discharged into cold water to obtain a copolyamide hot melt adhesive.

[0066] According to the test, the melting point of the copolyamide hot melt adhesive prepared above is 105° C., and the melt flow index is 21 g / 10 min.

[0067] The copolyamide hot melt adhesive prepared in Example 1 was pelletized and then deep-cold crushed by liquid nitrogen and sieved to obtain powder with a particle size of 80 to 170 μm. The acetate fabric and the three-proof fabric were powdered and bonded by a powdering process. The peel strength and the peel strength after washing three times at 40°C and the water washing loss rate were measured as shown in Table 1.

[0068] Table 1 Peel strength and water washing loss rate of copolyamide hot melt adhesive in Example 1

[0069]

[0070] Example 2

[0071] Caprolactam 4390.050 g (38.850 mol), adipic acid 1460.000 g (10.000 mol), succinic acid 177.000 g (1.500 mol), sebacic acid 3030.000 g (15.000 mol), dodecane diacid 3680.000 g (16.000 mol), tetradecane diacid 2928.000 g (12.000 mol), hexamethylenediamine 1740.000 g (15.000 mol), pentamethylenediamine 765.000 g (7.500 mol), polyetheramine (D400) 1200.000 g (3.000 mol), 4,4-diaminodicyclohexylmethane 378.000 g (1 g (1.800 mol), 1548.000 g (9.000 mol) of decanediamine, 3840.000 g (19.200 g), 50.272 g of antioxidant and 1759.524 g of water were added into a 50 L reactor, the temperature was raised to 100 ° C and then stirred, the temperature was continued to be raised to 175 ° C, and the pressure was controlled at 0.55 MPa to carry out salt-forming reaction for 3.0 hours. After the salt-forming reaction was completed, the temperature and pressure were continued to be raised to 255 ° C and 1.65 MPa to carry out polymerization reaction for 3.5 hours. After the polymerization reaction was completed, the pressure was released to 0 MPa at a rate of 0.005 MPa / 10s, and then it was allowed to stand for 1.5 hours; nitrogen was introduced and the material was discharged into cold water to obtain a copolyamide hot melt adhesive.

[0072] According to the test, the melting point of the copolyamide hot melt adhesive prepared above is 103° C., and the melt flow index is 22 g / 10 min.

[0073] The copolyamide hot melt adhesive prepared in Example 2 was pelletized and then cryogenically crushed by liquid nitrogen and sieved to obtain powder with a particle size of 80 to 170 μm. The acetate fabric and the three-proof fabric were powdered and bonded by a powdering process. The peel strength and the peel strength after washing three times at 40°C and the water washing loss rate were measured as shown in Table 2.

[0074] Table 2 Peel strength and water washing loss rate of copolyamide hot melt adhesive in Example 2

[0075]

[0076] Example 3

[0077] Caprolactam 3262.875 g (28.875 mol), adipic acid 1460.000 g (10.000 mol), succinic acid 200.600 g (1.700 mol), sebacic acid 2828.000 g (14.000 mol), dodecane diacid 3450.000 g (15.000 mol), tetradecane diacid 3416.000 g (14.000 mol), hexamethylenediamine 1740.000 g (15.000 mol), pentamethylenediamine 918.000 g (9.000 mol), polyetheramine (D400) 1800.000 g (4.500 mol), 4,4-diaminodicyclohexylmethane 315.0 00g (1.500mol), 1290.000g (7.500mol) of decanediamine, 3660.000g (18.300g), 97.362g of antioxidant and 1217.024g of water were added into a 50L reactor, the temperature was raised to 100°C and then stirred, the temperature was continued to be raised to 180°C, and the pressure was controlled to be 0.6MPa for salt-forming reaction for 3.0h. After the salt-forming reaction, the temperature and pressure were continued to be raised to 260°C and 1.65MPa for polymerization reaction for 3.5h. After the polymerization reaction, the pressure was released to 0MPa at a rate of 0.005MPa / 10s, and then allowed to stand for 2h; nitrogen was introduced and the material was discharged into cold water to obtain a copolyamide hot melt adhesive.

[0078] According to the test, the melting point of the copolyamide hot melt adhesive prepared above is 110° C., and the melt flow index is 25 g / 10 min.

[0079] The copolyamide hot melt adhesive prepared in Example 3 was pelletized and then cryogenically crushed by liquid nitrogen and sieved to obtain powder with a particle size of 80 to 170 μm. The acetate fabric and the three-proof fabric were powdered and bonded by a powdering process. The peel strength and the peel strength after washing three times at 40°C and the washing loss rate were measured as shown in Table 3.

[0080] Table 3 Peel strength and water washing loss rate of copolyamide hot melt adhesive in Example 3

[0081]

[0082] Example 4

[0083] Caprolactam 5071.440 g (44.880 mol), adipic acid 1460.000 g (10.000 mol), succinic acid 236.00 g (2.000 mol), sebacic acid 2222.000 g (11.000 mol), dodecane diacid 3910.000 g (17.000 mol), tetradecane diacid 3660.000 g (15.000 mol), hexamethylenediamine 1740.000 g (15.000 mol), pentamethylenediamine 841.500 g (8.250 mol), polyetheramine (D400) 2100.000 g (5.250 mol), 4,4-diaminodicyclohexylmethane 441.000 g (15.000 mol) g (2.100 mol), 1496.4.000 g (8.700 mol) of decanediamine, 3360.000 g (16.800 g), 132.692 g of antioxidant and 2123.067 g of water were added into a 50 L reactor, the temperature was raised to 100 ° C and then stirred, and the temperature was continued to be raised to 180 ° C. At the same time, the pressure was controlled at 0.6 MPa to carry out salt-forming reaction for 3.0 h. After the salt-forming reaction, the temperature and pressure were continued to be raised to 260 ° C and 1.65 MPa to carry out polymerization reaction for 3.5 h. After the polymerization reaction, the pressure was reduced to 0 MPa at a rate of 0.005 MPa / 10s, and then allowed to stand for 2 h; nitrogen was introduced and the material was discharged into cold water to obtain a copolyamide hot melt adhesive.

[0084] According to the test, the melting point of the copolyamide hot melt adhesive prepared above is 113° C., and the melt flow index is 23 g / 10 min.

[0085] The copolyamide hot melt adhesive prepared in Example 4 was pelletized and then cryogenically crushed by liquid nitrogen and sieved to obtain powder with a particle size of 80 to 170 μm. The acetate fabric and the three-proof fabric were powdered and bonded by a powder sprinkling process. The peel strength and the peel strength after washing three times at 40°C and the washing loss rate were measured as shown in Table 4.

[0086] Table 4 Peel strength and water washing loss rate of copolyamide hot melt adhesive in Example 4

[0087]

[0088] Comparative Example 1

[0089] Caprolactam 5071.440 g (44.880 mol), adipic acid 1460.000 g (10.000 mol), succinic acid 118.00 g (1.000 mol), sebacic acid 2222.000 g (11.000 mol), dodecane diacid 3910.000 g (17.000 mol), tetradecane diacid 3910.000 g (16.000 mol), hexamethylenediamine 1740.000 g (15.000 mol), pentamethylenediamine 841.500 g (8.250 mol), polyetheramine (D400) 2100.000 g (5.250 mol), 4,4-diaminodicyclohexylmethane 441.000 g (1 g (2.100mol), 1496.4.000g (8.700mol) of decanediamine, 3360.000g (16.800g) of dodecyl diamine, 133.322g of antioxidant and 2133.147g of water were added into a 50L reactor, the temperature was raised to 100°C and then stirred, the temperature was continued to be raised to 180°C, and the pressure was controlled at 0.6MPa for salt-forming reaction for 3.0h. After the salt-forming reaction was completed, the temperature and pressure were continued to be raised to 260°C and 1.65MPa for polymerization reaction for 3.5h. After the polymerization reaction was completed, the pressure was released to 0MPa at a rate of 0.005MPa / 10s, and then allowed to stand for 2h; nitrogen was introduced and the material was discharged into cold water to obtain a copolyamide hot melt adhesive.

[0090] According to the test, the melting point of the copolyamide hot melt adhesive prepared above is 96° C., and the melt flow index is 22 g / 10 min.

[0091] The copolyamide hot melt adhesive prepared in Comparative Example 1 was pelletized and then deep-cold crushed by liquid nitrogen and sieved to obtain powder with a particle size of 80 to 170 μm. The acetate fabric and the three-proof fabric were powdered and bonded by a powder sprinkling process. The peel strength and the peel strength after washing three times at 40°C and the water washing loss rate were measured as shown in Table 5.

[0092] Table 5 Peel strength and water washing loss rate of copolyamide hot melt adhesive in comparative example 1

[0093]

[0094] Comparative Example 2

[0095] Caprolactam 5590.585 g (49.545 mol), adipic acid 1460.000 g (10.000 mol), succinic acid 118.000 g (1.000 mol), sebacic acid 2424.000 g (12.000 mol), dodecane diacid 4140.000 g (18.000 mol), tetradecane diacid 3172.000 g (13.000 mol), hexamethylenediamine 1740.000 g (15.000 mol), pentamethylenediamine 612.000 g (6.000 mol), polyetheramine (D400) 1500.000 g (3.750 mol), 4,4-diaminodicyclohexylmethane 472.5 00g (2.250mol), 1419.000g (8.250mol) of decanediamine, 3960.000g (19.800g) of dodecyl diamine, 66.540g of antioxidant and 1596.965g of water were added into a 50L reactor, the temperature was raised to 100°C and then stirred, the temperature was continued to be raised to 170°C, and the pressure was controlled to 0.5MPa for salt-forming reaction for 3.0h. After the salt-forming reaction was completed, the temperature and pressure were continued to be raised to 260°C and 1.6MPa for polymerization reaction for 3h. After the polymerization reaction was completed, the pressure was released to 0MPa at a rate of 0.005MPa / 10s, and then it was allowed to stand for 1.5h; nitrogen was introduced and the material was discharged into cold water to obtain a copolyamide hot melt adhesive.

[0096] According to the test, the melting point of the copolyamide hot melt adhesive prepared above is 120° C., and the melt flow index is 21 g / 10 min.

[0097] The copolyamide hot melt adhesive prepared in Comparative Example 2 was pelletized and then cryogenically crushed with liquid nitrogen and sieved to obtain powder with a particle size of 80 to 170 μm. The acetate fabric and the three-proof fabric were powdered and bonded by a powder sprinkling process. The peel strength and the peel strength after washing three times at 40°C and the water washing loss rate were measured as shown in Table 6.

[0098] Table 6 Peel strength and water washing loss rate of copolyamide hot melt adhesive in comparative example 2

[0099]

[0100] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a copolyamide hot melt adhesive, characterized in that: The following steps are involved: The lactam, the dibasic acid, the diamine, the antioxidant and water are mixed to form a salt to obtain a first product; The first product is subjected to a polymerization reaction, and after the polymerization reaction is completed, the product is allowed to stand to obtain a copolyamide hot melt adhesive.

2. The method for preparing the copolyamide hot melt adhesive according to claim 1, characterized in that: The lactam is caprolactam; The dibasic acid is a mixture of adipic acid, succinic acid, sebacic acid, dodecane diacid and tetradecane diacid; The diamine is a mixture of hexamethylenediamine, pentamethylenediamine, polyetheramine, 4,4-diaminodicyclohexylmethane, decanediamine and dodecyldiamine.

3. The method for preparing the copolyamide hot melt adhesive according to claim 1, characterized in that: The antioxidant is at least one of 1098, 168, and 1010; The conditions of the salt-forming reaction are as follows: pressure of 0.5-0.6 MPa, temperature of 170-180° C., and time of 2-3 h.

4. The method for preparing the copolyamide hot melt adhesive according to claim 1, characterized in that: The molar ratio of the diamine to the lactam is 1:0.5-0.8; The molar ratio of the diamine to the dibasic acid is 1.02:1; The mass of the antioxidant is 0.2-0.5% of the total mass of the lactam, the dibasic acid and the diamine; The mass of the water is 5-8% of the total mass of the lactam, the dibasic acid and the diamine.

5. The method for preparing the copolyamide hot melt adhesive according to claim 2, characterized in that: The molar ratio of adipic acid to succinic acid in the dibasic acid is 1:0.1-0.2; The molar ratio of adipic acid to sebacic acid in the dibasic acid is 1:1.1-1.5; The molar ratio of adipic acid to dodecane diacid in the dibasic acid is 1:1.5-1.8; The molar ratio of adipic acid to tetradecane diacid in the dibasic acid is 1:1.2-1.

5.

6. The method for preparing the copolyamide hot melt adhesive according to claim 2, characterized in that: The molar ratio of hexamethylenediamine to pentamethylenediamine in the diamine is 1:0.4-0.6; The molar ratio of hexamethylenediamine to polyetheramine (D400) is 1:0.2-0.35; The molar ratio of hexamethylenediamine to 4,4-diaminodicyclohexylmethane is 1:0.1-0.15; The molar ratio of hexamethylenediamine to decanediamine is 1:0.5-0.6; The molar ratio of hexamethylenediamine to dodecyldiamine is 1:1.12-1.

32.

7. The method for preparing the copolyamide hot melt adhesive according to claim 1, characterized in that: The polymerization reaction conditions are as follows: pressure of 1.6-1.7 MPa, temperature of 255-260° C., and time of 3-4 h.

8. The method for preparing the copolyamide hot melt adhesive according to claim 1, characterized in that: After the polymerization reaction is completed, the pressure is released to 0 MPa, and the speed of the pressure release is 0.005 MPa / 10s; The standing time is 1.5 to 2 hours.

9. The copolyamide hot melt adhesive prepared by the method for preparing the copolyamide hot melt adhesive according to any one of claims 1 to 8.

10. Use of the copolyamide hot melt adhesive according to claim 9 in fabrics.